PENGARUH STRATEGI PAKEM TERHADAP HASIL BELAJAR IPA SISWA KELAS IV MIN LABUI - Faisal (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2017)
The purpose of the study was to determine the effect of the implementation of the PAKEM strategy on the science learning outcomes of the 4th grade students of MIN Labui and to determine whether there was an effect of the PAKEM strategy on the science learning outcomes of the fourth graders of MIN Labui. This study uses classroom action research, using Kurt Lewin's model. The results of the CAR research through the Influence of the Implementation of PAKEM Strategy on Science Learning Outcomes in Grade IV Students of MIN Labui in cycle I showed the average value of student evaluation was 6.42%. Student learning outcomes in cycle II were also not good, but the second cycle meeting students have had a slight change, students have dared to ask the teacher about natural resource material that they have not understood, the average value of students in cycle II is 7.10%. Teacher and student learning activities are maximized and in cycle III student learning outcomes already optimal which are 8.17%.